Tailoring oral targeted therapies dosage in lung cancer: A systematic review of pharmacokinetics studies on renal and hepatic impairment. - Harri Hardi; Zahra Fitrianti; Karen Elliora Utama; Ananda Pipphali Vidya; Nurul Gusti Khatimah; Kevin Aristyo; Hana Khairina Putri Faisal; Vivian Soetikno (PLoS ONE)
Background Lung cancer is the leading cause of cancer-related deaths worldwide, and stage IV lung cancer is frequently managed with targeted therapy. Renal and hepatic impairment frequently coexist with cancer, often requiring a reduction in targeted therapy dosage. This systematic review assesses the appropriateness of current targeted therapy dosage adjustments in individuals with hepatic and renal impairment by comparing package insert recommendations with available pharmacokinetic studies. Methods We reviewed the most recent guidelines from the National Comprehensive Cancer Network (NCCN) on the use of non-monoclonal antibody targeted therapy. We also examined all package inserts for information on dose adjustment in cases of hepatic and renal impairment. We then systematically searched for studies that involved pharmacokinetic analysis in populations with hepatic or renal impairment, as well as those undergoing hemodialysis and peritoneal dialysis. Results We identified 44 studies from 21 oral lung cancer therapies that met the inclusion criteria. We developed 13 new recommendations and updated 7 existing ones regarding targeted therapy dose adjustment in cases of hepatic and renal impairment compared to the information provided in the package insert. Several drugs have not published their pharmacokinetic results in a scientific journal, which limits access to their appropriateness. Moreover, there is a lack of research on pharmacokinetic analysis of targeted therapy in patients undergoing hemodialysis and peritoneal dialysis. Conclusions Adjusting the dosage of targeted therapy in hepatic and renal impairment based on pharmacokinetic analysis is essential to broaden the usage, improve effectiveness, and minimize side effects. Further pharmacokinetic research on the usage in unstudied populations is strongly advised. Prospero registration number CRD42024518123.